The Influence of Tiktok Live Streaming and Content Marketing on Intention to Purchase Streetwear Products - Farhan Aditya; Didin Ahmad Sirojudin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study analyzes the effect of TikTok live streaming and content marketing on purchase intention. Using a quantitative approach, data were collected through a survey of 150 consumers who actively watching content and live streams on TikTok. The results show that both TikTok live streaming and content marketing positively and significantly influence purchase intention. Live streaming fosters real-time interaction, enhancing consumer trust and engagement, while content marketing builds strong brand awareness through creative and informative content. Together, these strategies reinforce purchase decisions, indicating that social media is an effective marketing tool for boosting purchase intention in the fashion sector. The research recommends optimizing both strategies to increase sales and strengthen consumer loyalty.